2020
DOI: 10.3389/fpubh.2020.565849
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Influencing Factors of Pediatric Medical Staff During the COVID-19 Outbreak

Abstract: Objective: To evaluate the health-related quality of life (HRQoL) status and explore its associated factors in pediatric medical staff during the COVID-19 epidemic so as to provide fundamental evidence for clinicians and administrators to formulate targeted intervention measures to improve the HRQoL and mental health status in pediatric medical staff during this, and future pandemics. Methods: A cross-sectional study was conducted to investigate the HRQoL of pediatric medical staff. Univariable and multivariab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
(23 reference statements)
0
17
2
3
Order By: Relevance
“…Despite the significance of the stress-related COVID -19, data are lacking about its association with healthrelated quality of life. Thus, there is an utmost need to study the association of stress-related to COVID -19 with Health-Related Quality of Life (HR-QOL) to assist the policymakers in designing adequate specific preventive interventions/measures to avoid hampering of Health-Related Quality of Life (HR-QOL) among masses (12). COVID-19 pandemic plays a vital role in exerting psychological and physiological stress on common men & women, social organizations and businesses globally.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significance of the stress-related COVID -19, data are lacking about its association with healthrelated quality of life. Thus, there is an utmost need to study the association of stress-related to COVID -19 with Health-Related Quality of Life (HR-QOL) to assist the policymakers in designing adequate specific preventive interventions/measures to avoid hampering of Health-Related Quality of Life (HR-QOL) among masses (12). COVID-19 pandemic plays a vital role in exerting psychological and physiological stress on common men & women, social organizations and businesses globally.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse psychological responses such as high levels of anxiety, depression, and post-traumatic stress disorders may occur among front-line medical staff who are in direct contact with the COVID-19 patients ( Chersich et al, 2020 ; Nochaiwong et al, 2020 ). Moreover, recent studies have demonstrated that the outbreak of COVID-19 had a significant impact on QoL of health care workers ( Huang et al, 2020 ; Suryavanshi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the morbidity of COVID-19 in children was not high, the above behaviors indirectly brought an increased workload, a high risk of infection and psychological distress to pediatric medical workers who bore new psychological pressure again. Third, it was reported that the health-related quality of life of pediatric medical workers declined during the COVID-19 epidemic (Huang et al, 2020), 10.3% of respondents represented moderate or severe psychological impact, and 4.0% showed severe anxiety symptoms (Zhang et al, 2020), which was higher than the general Chinese population prevalence of severe anxiety symptoms (2.3%) during the epidemic . Also, our investigation (Liu et al, 2020) found that depression (14.8%) and anxiety (18.3%) were present to varying degrees among pediatric medical workers across the country.…”
Section: Introductionmentioning
confidence: 95%
“…According to the previous studies, those who had high education (master and above), senior titles or aged between 30 years old and 60 years old were prone to psychological problems (Huang et al, 2020;Liu et al, 2020). Compared with nurses, doctors suffered from more stress due to first physical examination and medical decisions (Huang et al, 2020). Meanwhile, those who had been exposed to confirmed or suspected COVID-19 patients or worked in Hubei province faced a greater psychological burden (Huang et al, 2020;Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation